Understanding the Importance of Time Management for Students - Rokhila Bafoeva; Makhmudova Madina Saidovna (Journal of Innovation in Education and Social Research, 2024)
Time management is a fundamental skill that influences a student's academic success, personal development, and overall well-being. This paper explores the significance of time management for students,its role in academic performance, reducing stress, and fostering personal growth. By understanding the impact of effective and ineffective time management, students can better prepare themselves for future challenges and success. Strategies for managing time effectively are discussed, offering practical tools that can help students optimize their schedules and achieve a balanced lifestyle.